Impact of tumor infiltrating lymphocytes and lymphoid follicle formation on patient survival following surgery for lung squamous cell carcinoma. Issue 2 (18th December 2018) - Nishihira, Morimichi; Nakazato, Yoshimasa; Maeda, Sumiko; Inoue, Takashi; Araki, Osamu; Karube, Yoko; Chida, Masayuki
Abstract : Background: Tumor infiltrating lymphocytes (TILs) are known to correlate with the prognosis of patients affected by a variety of cancer types. We evaluated TILs in patients who underwent surgery for lung squamous cell carcinoma (SCC). Methods: Specimens obtained from patients during resection of lung SCC were examined for TIL density, lymphoid follicle formation, PD‐L1 expression, and the appearance of regulatory T cells (Tregs). Results: We enrolled 72 patients who underwent surgery for SCC (TIL grades 0, 1, and 2: 29, 18, and 25, respectively). Lymphoid follicles were observed in 13 (18.1%) patients and 8 were positive for Tregs, which were always observed in association with lymphoid follicles ( P < 0.001). Multivariate analysis revealed that lymphoid follicle formation, the appearance of Tregs, pathological stage, and pleural invasion were independent prognostic factors related to overall survival, whereas TIL density and PD‐L1 expression were not. Conclusion: SCC patients with lymphoid follicle formation accompanied by Tregs show poor survival following lung resection surgery.